Fibrin/fibrinogen degradation products in children with renal disease. Issue 2 (February 1974) - Uttley, W. S.; Maxwell, Heather; Cash, J. D.
Abstract : Fibrin/fibrinogen degradation products (FDP) were measured in the serum and urine of children with various forms of renal disease. Serum FDP was raised both with nephrosis and with active proliferative nephritis. Urine FDP was rarely present in nephrosis but was significantly increased during the active phase of proliferative nephritis and also in urinary tract infection with frank haematuria. Urinary FDP correlated with total urinary protein in proliferative nephritis but not in nephrosis, nor did it correlate with serum FDP in either condition. The major application of urinary FDP determination in clinical practice is as an indicator of activity and possible response to treatment in the management of active proliferative nephritis.